1997
DOI: 10.1093/milmed/162.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Soldier Performance and Strenuous Road Marching: Influence of Load Mass and Load Distribution

Abstract: Fifteen male soldiers performed six maximal-effort, 20-km road marchers. They carried load masses of 34, 48, and 61 kg, using a standard military backpack with frame or an experimental doublepack. March times decreased as mass increased and were faster with the standard pack than with the double-pack. The doublepack resulted in less low back discomfort and a lower incidence of blisters at the highest load, but also resulted in more discomfort in the neck and hips. Neither load mass nor pack type affected soldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 0 publications
0
70
1
Order By: Relevance
“…Both of these factors have been shown by other studies to be possible reasons for such increase. The important role that increases in maximum braking force play in the development of blisters is highlighted again in a study by Knapik et al (1997b).…”
Section: Changes Observed To the Maximum Braking Forcementioning
confidence: 95%
See 1 more Smart Citation
“…Both of these factors have been shown by other studies to be possible reasons for such increase. The important role that increases in maximum braking force play in the development of blisters is highlighted again in a study by Knapik et al (1997b).…”
Section: Changes Observed To the Maximum Braking Forcementioning
confidence: 95%
“…The main interest with this parameter in respect to LCS design is that increased sheer forces that act on the foot will 'increase the probability of blisters during physical activity' (Knapik et al, 1997a). Foot blisters are the most common load carriage related injury and can also be debilitating (Knapik et al, 1997b;Reynolds et al, 1999). Load carriage has also been shown to increase blister incidence independently to other factors, with Knapik et al (1997a) suggesting that load carriage increases the pressure on the skin and causes more movement between the foot and boot through higher propulsive and braking forces, thus increasing the risk of blister occurrence.…”
Section: Changes Observed To the Maximum Braking Forcementioning
confidence: 99%
“…The anterior-posterior force helps slow the body down during the initial part of the gait cycle (Birrell and Haslam, 2010). Its increase seems to be related to blister development (Knapik et al, 1997). Birrel and Haslam (2010) suggested that load carriage increases the pressure on the skin and causes more movement between the foot and the shoe through higher propulsive and braking forces, thus increasing the risk of blister.…”
Section: Rearfoot Regionmentioning
confidence: 99%
“…Knapik et al assessed the effect of backpack and double pack. They reported that double pack caused less discomfort in low back, lower incidence of blisters, but it resulted in pain in neck and hips and it took longer to complete the march with wearing the double pack [27]. Also, Mackie et al evaluated the influence of four backpacks on perceived exertion and discomfort.…”
Section: Can Different Designs Of Load Carriage Systemsmentioning
confidence: 99%